POTENSI PROGRAM CABRI 3D UNTUK MENDUKUNG PEMBELAJARAN GEOMETRI ANALIT DI PERGURUAN TINGGI - Buchori, Achmad (AKSIOMA, 2011)
In IKIP PGRI semarang especially lecturer mathematic and fisic programe,  I think not more lecturer  use software mathematic programe to improve creativity student,  many student can not visuality many problem mathematic, especially about geometri topic. At this research get population is student grade 3 and  class 3B is sample. Many student very interesting to practice with cabri 3D software because they are not use before. After practice software many student think that software cabri 3D very important to visualitiy intersection two or more in geometri analit topic. After post test geometri analit, 3B class get average value 76,40 more good than average value all class is 70,25. And than motivation dan creativity student in class experiment get 73,24% more good compare regular class is 68,30% following questioner test APKG IKIP PGRI Semarang. I hope with cabri 3D programme can make many lecturer, teacher and student like mathematic lesson especially geometri analit topic. Keyword: Cabri 3D, creativity, mathematic learning, visuality and exploration.